Self-aligned silicon tips coated with diamondlike carbon - Lee, S; Lee, S; Lee, S; Jeon, D; Lee, KR (A V S AMER INST PHYSICS, 1997)
Silicon field emitter tips are coated with diamondlike carbon (DLC) film. Argon-ion bombardment of the tips increased the aspect ratio and helped uniform DLC coating. Using DLC-coated tips, we have fabricated a self-aligned gated field emission array. (C) 1997 American Vacuum Society.
Keywords: FIELD